Antagonismo cooperativo na provis\~ao de cuidado a usuários de Drogas no Distrito Federal: Conflitos e parcerias entre CAPS AD e CT - Maria Paula Gomes dos Santos; Roberto Rocha Coelho Pires (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– The article is based on qualitative research carried out by the authors at the seven Psychosocial Care Centers for Alcohol and other Drugs (CAPS AD) in the Federal District, in order to observe the implementation of the Ministry of Health Policy for Comprehensive Care for Users of Alcohol and Other Drugs, 2003; as well as the resumption, in this territory, of an intense controversy, established at national level, which opposes, on the one hand, defenders of the model of care advocated by this policy - territorial based care, guided by harm reduction - and, on the other , entrepreneurs of Therapeutic Communities (TCs) - civil society institutions, often religious, that provide assistance to people who make problematic uses of alcohol and other drugs, through hospitalizations and with the aim of promoting abstinence.
Keywords: I18; I38; N36; 330; drug policy; health policy